Influence of socio-demographic characteristics on perception on climate change by fisher’s along lake Victoria beaches in Siaya County, Kenya. - Abura, Beatrice A.; Tonui, Warkach Kipkorir; Hayombe, Patrick O. (International Journal of Scientific Research and Innovative Technology, 2017)
Perception on climate change is increasing globally with increase on knowledge and its effects to individuals. The aim of this study was to evaluate the influence of socio demographic characteristics on climate change by fishers along Lake Victoria beaches in Siaya County. A sample of 385 household heads (proportionately selected) was used. Primary data was collected and analyzed quantitatively by the help of a logistic regression model. With a logistic regression model having coefficients which provided the relationship between the probability (socio-demographic characteristics) and influences on predictors (perception on climate change), the R2 (Nagelkerke) of 0.704 showed that there was a strong relationship between socio-demographic characteristics and perception on climate change. There is need to know how relationship between socio-demographic characteristics and perception on climate change as such information help in identifying problems, solutions and challenges on how climate change resilience can be achieved.
Keywords: Perception; Fisher’s; Lake; Victoria; Beaches; Siaya; County; Kenya